In Vitro Differentiation of Bone Marrow Mesenchymal Stem Cells into Neuron-Like Cells by Cerebrospinal Fluid Improves Motor Function of Middle Cerebral Artery Occlusion Rats - Ye, Ying; Peng, Yi-ran; Hu, Shu-qun; Yan, Xian-liang; Chen, Juan; Xu, Tie (Frontiers in Neurology, 2016)
Bone marrow mesenchymal stem cells (BMSCs) represent a promising tool for stem cell-based therapies. However, the majority of BMSCs transplants only allow for limited recovery of the lost functions. We previously found that human cerebrospinal fluid (hCSF) is more potent than growth factors in differentiateing human BMSCs into neuron-like cells in vitro. In this study, we studied the effect of transplantation of rat BMSC-derived neuron-like cells induced by hCSF into rat brain with middle cerebral artery occlusion (MCAO). The survival and differentiation of the transplanted cells were determined using immunofluorescence staining of bromodeoxyuridine. The recovery of neurological function were observed by the modified neurological severity score (modified NSS) at 4d, 15d, and 32d after cell transplantation, HE staining for determination of the infarct volume at 32d after cell transplantation. Transplantation of BMSC-derived neuron-like cells or BMSCs significantly improved indexes of neurological function and reduced infarct size in rats previously subjected to MCAO compared with those in the control group.Remarkably, 32 days after transplantation, rats treated with BMSC-derived neuron-like cells presented a smaller infarct size, higher number of neuron-specific enolase-positive and BrdU-positive cells, and improved neurological function compared to BMSC group. Our results demonstrate that transplantation of hCSF-treated BMSC-derived neuron-like cells significantly improves neurological function and reduces infarct size in rats subjected to MCAO. This study may pave a new avenue for the treatment of MCAO.